Le mémoire de Sodarcan, Inc. relatif à l’article 42 du groupe de travail sur l’épargne au Québec - Parizeau, Robert (Assurances)

(untitled) (HEC Montréal, 1981)
The Quebec Government has appointed a committee to enquire into the various forms of savings in the Province. A report has been submitted to the Assemblée Nationale recently and a request has been addressed to the public for advice on the recommendations. Article 42 deals particularly with the Government's interest in reinsurance. A suggestion is made to the effect that the Government should study the possibility of participating, as a minority shareholder and for a limited period of time, in the financing of a reinsurance company dealing in damage insurance. Sodarcan, Inc. has sent to the Deputy Minister of the Ministère des Consommateurs, Coopératives et Institutions financières the following report dealing with the recommendations made by the committee. We have pleasure in publishing it in order that our readers may know the attitude taken by a Canadian group which has a thorough and practical knowledge of insurance and reinsurance in Canada.